Ballariel 23 октября 2019 в 11:35

(2x-3)(5x+2)=(2x-3)(3x-8)Решите пожалуйста! Нужно и решение и ответ!

(2x - 3)(5x + 2) = (2x - 3)(3x - 8)  |  :(2x - 3)          2x - 3 = 0
                                                                                       x₁ = 1,5
5x + 2 = 3x - 8
2x = -10
 x₂ = -5

Проверим:    (2*(-5) - 3)(5*(-5) + 2) = (2*(-5) - 3)(3*(-5) - 8)
                                           -13 * (-23) = -13* (-23) 
                                                      299 = 299

Ответ: {-5; 1,5}

( 2х - 3 )( 5х + 2 ) = ( 2х - 3 )( 3х - 8 )
( 2х - 3 )( 5х + 2 - 3х + 8 ) = 0
( 2х - 3 )( 2х + 10 ) = 0
2х - 3 = 0
Х = 1,5
2х + 10 = 0
Х = - 5
Вычисления
Для комментирования необходимо зарегистрироваться на сайте